Eocene whales from the La Meseta Formation, Antarctica: Clues on the radiation of Pelagiceti in the Southern Hemisphere - Buono, Mónica Romina; Fernández, Marta Susana; Bona, Paula; Santillana, Sergio Nestor; Arnaudo, Eugenia; Puerta, Pablo; Reguero, Marcelo Alfredo
Eocene cetacean records, mainly from the northern hemisphere, documented one of the most outstanding processes of mammalian evolution such as the shift from terrestrial to an aquatic lifestyle. On the other hand, Eocene Southern Hemisphere records are significant in documenting the other critical episode in cetacean evolution: the radiation of fully aquatic whales (i.e. Pelagiceti). Pelagiceti, spread into temperate latitudes far from the Tethys Sea, and include the Basilosauridae and Neoceti the group comprising the modern lineages Mysticeti and Odontoceti. The most significant Pelagiceti records from the Southern Hemisphere were recovered from Eocene beds of the La Meseta Formation (Marambio = Seymour Island, Antarctica), and consists in fragmentary basilosaurid materials and a single specimen of the earliest member of Mysticeti, the holotype of Llanocetus denticrenatus. Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Bona, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Santillana, Sergio Nestor. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Arnaudo, Eugenia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Puerta, Pablo. Museo Paleontológico Egidio Feruglio; Argentina Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección ...